Applied Buddhism in the Digital Era and Its Role in Promoting Religious Moderation: Evidence From Negerikaton District - Susanto Susanto; Euis Dewi Yuliana; Hesti Sadtyadi (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2026)
Abstrak Era digital telah membawa transformasi signifikan dalam praktik keagamaan dan pola interaksi sosial, yang sekaligus menghadirkan peluang dan tantangan dalam membangun moderasi beragama di tengah masyarakat multikultural. Teknologi digital memperluas akses terhadap pengetahuan keagamaan dan memperkuat partisipasi komunitas, namun juga berpotensi mempercepat penyebaran paham keagamaan yang intoleran dan ekstrem. Penelitian ini bertujuan untuk mengeksplorasi peran Applied Buddhism di era digital dalam mempromosikan moderasi beragama di kalangan umat Buddha di Kecamatan Negerikaton, Kabupaten Pesawaran, Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan menganalisis implementasi praktis ajaran Buddha dalam kehidupan sehari-hari umat, yang diperkaya melalui pemanfaatan media dan teknologi digital dalam konteks komunitas lokal. Data dikumpulkan melalui observasi, wawancara mendalam, dan analisis dokumentasi, kemudian dianalisis secara tematik. Hasil penelitian menunjukkan bahwa Applied Buddhism, menekankan pengembangan etika, disiplin spiritual, dan kebijaksanaan melalui praktik seperti mindfulness dan meditasi, berperan penting dalam membentuk sikap keberagamaan yang moderat serta memperkuat relasi sosial yang harmonis. Media digital tidak hanya dimanfaatkan sebagai sarana komunikasi, tetapi juga sebagai platform pendukung dalam internalisasi nilai-nilai Buddhis seperti kasih sayang (karuṇā), pengendalian diri, dan keseimbangan dalam interaksi antarumat beragama. Secara teoretis, penelitian ini berkontribusi pada kajian sosiologi agama dengan mereposisi Applied Buddhism sebagai pendekatan keagamaan yang kontekstual dan adaptif terhadap tantangan era digital. Kata Kunci: Applied Buddhism; Moderasi Beragama; Era Digital; Buddhisme; Indonesia Abstract The digital era has brought significant transformations in religious practices and patterns of social interaction, presenting both opportunities and challenges in fostering religious moderation within multicultural societies. Digital technologies have expanded access to religious knowledge and enhanced community participation; however, they have also facilitated the rapid dissemination of intolerant and extremist religious discourses. This study aims to explore the role of Applied Buddhism in the digital era in promoting religious moderation among Buddhist communities in Negerikaton District, Pesawaran Regency, Indonesia. Employing a qualitative approach, this research examines the practical implementation of Buddhist teachings in the everyday lives of adherents, enriched by the use of digital media and technologies within a local community context. Data were collected through observation, in-depth interviews, and document analysis, and were subsequently analyzed using thematic analysis. The findings indicate that Applied Buddhism emphasizing the cultivation of ethics, spiritual discipline, and wisdom through practices such as mindfulness and meditation plays a significant role in shaping moderate religious attitudes and strengthening harmonious social relations. Digital media are utilized not only as channels of communication but also as supportive platforms for the internalization of Buddhist values, including compassion (karuṇā), self-restraint, and balance in interreligious interactions. Theoretically, this study contributes to the sociology of religion by repositioning Applied Buddhism as a contextual and adaptive religious approach in response to the challenges of the digital era. Key Words: Applied Buddhism; Religious Moderation; Digital Era; Buddhism; Indonesia